Mechanisms of allergic disease – environmental and genetic determinants for the development of allergy. Issue 5 (May 2015) - Campbell, D. E.; Boyle, R. J.; Thornton, C. A.; Prescott, S. L.
Summary Allergic disease can be viewed as an early manifestation of immune dysregulation. Environmental exposures including maternal inflammation, diet, nutrient balance, microbial colonization and toxin exposures can directly and indirectly influence immune programming in both pregnancy and the postnatal period. The intrauterine microclimate is critical for maternal and fetal immunological tolerance to sustain viable pregnancy, but appears susceptible to environmental conditions. Targeting aspects of the modern environment that promote aberrant patterns of immune response is logical for interventions aimed at primary prevention of allergic disease. Defining the mechanisms that underpin both natural and therapeutic acquisition of immunological tolerance in childhood will provide insights into the drivers of persistent immune dysregulation. In this review, we summarize evidence that allergy is a consequence of intrauterine and early life immune dysregulation, with specific focus on contributing environmental risk factors occurring preconception, in utero and in the early postnatal period. We explore the immunological mechanisms which underpin tolerance and persistence of allergic disease during childhood. It is likely that future investigations within these two domains will ultimately provide a road map for the primary prevention of allergic disease.